Dialogue Interpreting and the Distribution of Responsibility - Wadensjö, Cecilia (HERMES - Journal of Language and Communication in Business, 2017)
The sense-making work carried out by anyone in interaction can be described as based on different aspects of meaning, basically the propositional meaning of talk and the interactional or situated meaning of words spoken. Moreover, in a conversation involving three or more persons, sense is arguably made also on the basis of the participation framework (Goffman, 1981), continuously negotiated in and by talk. This composes a theoretical platform for the analysis of the distribution of responsibility in an interpreter-mediated encounter; responsibility for the substance and for the progression of talk. The paper suggests an interactionistic, non-normative, dialogical approach to studies of interpreter-mediated talk for a deepened, developed understanding of the interpreter’s role in face-to-face interaction.